News Commentaries March 1960 - Abrahams, Peter (My University, 1960)
List of broadcasts for the months of March 1960
57 pgs. Typescript, letter-sized, sepia-toned, in fairly good condition.
Keywords: West Indies Federation; Sugar Industry – Jamaica; Rose Hall Sugar Factory, Montego Bay; Industrial relations; Police – Jamaica; Police – Complaints against – Jamaica; Legislation – Jamaica; Health